2022
DOI: 10.1111/1748-8583.12476
|View full text |Cite
|
Sign up to set email alerts
|

What do they think of me? Professional diversity, meta‐stereotype negativity, suspicion, and counterproductive work behaviour

Abstract: Relatively little is known about the role of diversity in counterproductive work behaviour (CWB). Drawing on social categorisation theory, we develop and investigate a model of professional diversity on interpersonal CWB through the mediating role of suspicion and examine the role of perceived status differences as an important moderator of this indirect effect. Data from a sample of 63 United States healthcare teams (study 1) and 190 working professionals (study 2) suggest that professional diversity is posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 194 publications
(230 reference statements)
0
2
0
Order By: Relevance
“…Counterproductive work behaviors are actions committed by employees in the workplace that intentionally harm organizational interests or other members associated with organizational interests ( Bennett and Robinson, 2000 ) and include overt aggression and stealing, handling personal business during work hours, intentional failure to follow instructions and misassignments, and other more negative actions that are directly detrimental to the organization’s functions and assets ( Mitchell et al, 2022 ). Conservation of Resources Theory suggests that individuals are motivated to protect or compensate for resources when faced with the threat of resource loss ( Hobfoll, 1989 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Counterproductive work behaviors are actions committed by employees in the workplace that intentionally harm organizational interests or other members associated with organizational interests ( Bennett and Robinson, 2000 ) and include overt aggression and stealing, handling personal business during work hours, intentional failure to follow instructions and misassignments, and other more negative actions that are directly detrimental to the organization’s functions and assets ( Mitchell et al, 2022 ). Conservation of Resources Theory suggests that individuals are motivated to protect or compensate for resources when faced with the threat of resource loss ( Hobfoll, 1989 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…With the development of organizational behavior research, more and more studies have gradually shifted from focusing on employees’ task performance to employees’ extra-role behaviors. Among them, counterproductive work behaviors and organizational citizenship behaviors are two very common and highly relevant extra-role behaviors in management practice, the former focusing on spontaneous behaviors that deplete the organization or members’ interests ( Mitchell et al, 2022 ), and the latter focusing on spontaneous or mutually supportive behaviors that enhance organizational performance ( Qiu and Dooley, 2022 ). Research has shown that leadership behaviors are important antecedents that influence employees’ behavioral decisions ( Carter and Baghurst, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Duval et al (2021) determinaron siete temáticas que emergieron del análisis de contenido de los vídeos de Tik Tok analizados: información de la vida cotidiana, romper estereotipos, gamificación, terapia y rehabilitación, desafíos imposibles y ventajas de la diversidad. Otras redes sociales en auge como Instagram, si bien no han sido el propósito de estudio de investigaciones en materia de educación inclusiva para alumnado con TEA, sí que han sido señaladas como medios apropiados para mitigar estereotipos asociados con la diversidad funcional (Mitchell et al, 2022).…”
Section: Tipo De Información Ofrecida Por Las Fuentesunclassified